Electrochemical dissolution behavior of heat treated laser solid formed Inconel718. (15th August 2020) - Zhang, Yufeng; Lin, Xin; Yu, Jun; Guo, Pengfei; Li, Jiaqiang; Qin, Tuo; Liu, Jianrui; Huang, Weidong
Highlights: Phase distribution of the laser solid formed (LSF) Inconel718 after double aging (DA) heat treatment (DA-LSF Inconel718) presents the multi-tube structure. The electrochemical dissolution of vertical plane (VP) and horizontal plane (HP) in the DA-LSF Inconel718 was uneven. γ″ phases in the DA-LSF Inconel718 hindered the dissolution of γ matrix in the inter-dendritic region. The electrochemical anisotropy of DA-LSF Inconel718 is affected by the multi-tube phase distribution. The surface quality of DA-LSF Inconel718 can be effectively improved by electrochemical machining. Abstract: Microstructure characteristic and its effects on electrochemical dissolution behavior of horizontal plane (HP) and vertical plane (VP) in the laser solid formed (LSF) Inconel718 alloy after double aging (DA) heat treatment (DA-LSF Inconel718) were investigated. Compared to the as-deposited one, DA-LSF Inconel718 shows more phases and presents electrochemical anisotropy between HP and VP including the polarization curves, current efficiency curves and surface roughness. It is caused by different electrochemical dissolution processes on HP and VP and proved that surface energy has no obvious effect. Three models were proposed to illustrate electrochemical dissolution behavior, surface formation mechanism and electrochemical anisotropy, respectively.